Physical and mechanical behavior of hot mix asphalt mixtures incorporating WEO (LACCEI, 2024)
There is a complex environmental problem due to the inadequate treatment of industrial waste. The main drawback corresponds to storage, since there are no spaces to be disposed of. One of the pillars of the 2030 agenda corresponds to responsible production and consumption (SDG 12), being the justification that motivated the research on asphalt incorporating different percentages of WEO burned engine oil. Two hot mix asphalt designs were carried out, the first design to determine the optimum percentage of asphalt cement to be used and the second design to determine a hot mix asphalt with the incorporation of burnt oil from vehicle engines in percentages of 1.00%, 1.25%, 4.00% and 7.00%. There were 27 briquettes made to evaluate the stability, flow and density by means of the Marshall test. In addition, 12 normative tests of the Ministry of Transport and Communications were carried out for the fine and coarse aggregates used. The results indicated that the optimum percentage of PEN 85/100 asphalt cement is 6.50%, and considering the different percentages of WEO incorporation, they present stable values with an addition of 4.00%. From an economic analysis, the incorporation of WEO in the MAC raises production costs compared to the conventional mix, but from an environmental analysis it is highly favorable for its reuse at the national level.